Sustainable transport : new trends and business practices / Paulina Golinska, Marcin Hajdul - Golinska, Paulina
The scope of the book includes set of solutions which show different stakeholders’ viewpoints on sustainability. It points out how the transport operations organized and conducted in companies and regions might be consistent with the concept of sustainable development. The scope of the book takes into consideration trade-off relations between actors directly and indirectly involved in transport networks. Therefore, the authors present, in individual chapters, innovative approach to eco-friendly organization and coordination of transport processes, as well as management of transport networks.